Marketing strategy, technological innovation and inventory management towards Malaysia’s food industry performance - Tengku Auwalul Hawa, Yahya; Diyana, Kamarudin; Nor Suraini, Mohd Hassan (Future Academy, 2019)
Although the food industry is considered to be one of the sectors that contribute to the increase in country’s economy, research has also found that a relative 26.16% of independent restaurants failed during the first year of operation due to several factors such as failure to implement innovation in the management. This paper aims to study the significant relationship between factors that influenced and affected the performance of restaurants in Malaysia. The attributes were classified as marketing strategy, technological innovation and inventory management in the business itself. Three regions were utilized as specific research samples, specifically Kuantan, Temerloh and Rompin, which is the eastern part of Malaysia. The research found that there is a correlation between marketing strategy, technological innovation and inventory management to restaurant performance. Branding, product marketing, price considerations and location, all form part of the customer proposition. The study ascertained that the role of the marketing channels not only focuses on the demand satisfaction by offering goods, but also need to stimulate demand through information, creating proximity and promotion by customer.